YouTube as a source of language input: Early findings on children’s L2 acquisition - Pakaja, Marina; Ninsiana, Widhiya; Ramadhani, Dian Puspita; Husain, Nur Arifah A. (Research and Social Study Institute, 2024)
Evidence on how YouTube contributes to children’s second language (L2) acquisition remains limited, particularly in early childhood settings. This study examines the impact of YouTube and the factors shaping L2 learning among children. Using an exploratory descriptive approach with two participants aged 3 and 5, the study indicates that guided exposure to target-language YouTube content may support incidental gains in vocabulary, common expressions, and context-appropriate language use. Several factors appear to be associated with outcomes: (1) age, with preschoolers showing readiness to uptake novel forms; (2) presentation and input quality, including curated resources and caregiver support; (3) children’s intrinsic motivation to view and imitate; and (4) first-language (L1) influence, which can both facilitate and constrain transfer to L2. The findings suggest that parents and educators should provide active mediation, select developmentally appropriate content, and pair media exposure with offline interaction to enhance the meaningfulness of input. Given the small scale of this study, conclusions should be interpreted cautiously; future research with larger samples and stronger designs is recommended to validate and extend these preliminary insights.